Workshop Penggunaan Instagram Sebagai Strategi Bisnis Pemasaran Digital Bagi Rismada (Remaja Masjid Raudhatul Huda) - Emeilia, Rindana Intan; Andhikasari, Rosiana; Muntazah, Arina; ., Novalia; Aziz, Abdul (CV. ITTC INDONESIA, 2024)
One of the social media most used by teenagers is Instagram. Indonesia is in fourth place as the country with the largest Instagram users in the world. The number of Instagram users in Indonesia reached 89.15 million. Reasons for using Instagram include social interaction, filling free time, and knowing what other people are talking about. There are still many teenagers who don't understand the potential of Instagram as a digital marketing tool for running a business. In fact, teenagers who are the younger generation have a great opportunity to become successful young entrepreneurs by utilizing digital platforms such as Instagram. The ability and skills to use Instagram as a digital marketing medium also enable teenagers to prepare themselves to face the demands of an increasingly digital world of work. This Community Service Partner is Raudhatul Huda Mosque Youth (Rismada) located at Jl. Dr. Ciptomangunkusumo, Gg. H. Ripuh, RT 002 RW 009, North Paninggilan, Ciledug District, Tangerang City 15153. Rismada is a community service program partner which is classified as an economically/socially unproductive partner. The routine activities that Rismada usually carries out are religious activities and social activities. The community service team provided workshops on basic concepts of business strategy, digital marketing and business use of Instagram; (b) providing workshops by practicing the use of Instagram features, especially Instagram business, to carry out digital marketing business strategies. Activities carried out include, for example, creating an Instagram business account (Instagram ads), optimizing the features on Instagram business and creating interesting content; (c) Providing training and assistance to participants during the workshop activities.